A holistic organizational behaviour model for organization renewal - M. L. Watkins; A. L. Barnard (South African Journal of Business Management, 1989)
There is a need to identify the dependent and independent variables that play a role in organizational renewal. The scientific basis of previous attempts to identify these variables are questionable as they represent the haphazard inclusion of some contextual variables. A holistic view of approaches to organization theory, and its integration with contemporary organization models, makes it possible to scientifically develop and describe a holistic model of organizational behaviour. The model indicates that organizations are composed of human, strategic, technological, control-and-motivation and boundary subsystems. The interaction between these subsystems manifests itself in complex organizational processes which create a climate and culture of shared norms and values. The model identifies those dependent and independent variables which should be considered during renewal attempts. An empirical investigation of the practical value of the model shows that, by using the model as a frame of reference for renewal, positive change can be facilitated in various subsystems and processes. The model can therefore successfully be applied in the practice of organization renewal.
Keywords: 650